Azithromycin attenuates myofibroblast differentiation and lung fibrosis development through proteasomal degradation of NOX4. Issue 8 (3rd August 2017) - Tsubouchi, Kazuya; Araya, Jun; Minagawa, Shunsuke; Hara, Hiromichi; Ichikawa, Akihiro; Saito, Nayuta; Kadota, Tsukasa; Sato, Nahoko; Yoshida, Masahiro; Kurita, Yusuke; Kobayashi, Kenji; Ito, Saburo; et al.
ABSTRACT: Accumulation of profibrotic myofibroblasts is involved in the process of fibrosis development during idiopathic pulmonary fibrosis (IPF) pathogenesis. TGFB (transforming growth factor β) is one of the major profibrotic cytokines for myofibroblast differentiation and NOX4 (NADPH oxidase 4) has an essential role in TGFB-mediated cell signaling. Azithromycin (AZM), a second-generation antibacterial macrolide, has a pleiotropic effect on cellular processes including proteostasis. Hence, we hypothesized that AZM may regulate NOX4 levels by modulating proteostasis machineries, resulting in inhibition of TGFB-associated lung fibrosis development. Human lung fibroblasts (LF) were used to evaluate TGFB-induced myofibroblast differentiation. With respect to NOX4 regulation via proteostasis, assays for macroautophagy/autophagy, the unfolded protein response (UPR), and proteasome activity were performed. The potential anti-fibrotic property of AZM was examined by using bleomycin (BLM)-induced lung fibrosis mouse models. TGFB-induced NOX4 and myofibroblast differentiation were clearly inhibited by AZM treatment in LF. AZM-mediated NOX4 reduction was restored by treatment with MG132, a proteasome inhibitor. AZM inhibited autophagy and enhanced the UPR. Autophagy inhibition by AZM was linked to ubiquitination of NOX4 via increased protein levels of STUB1 (STIP1 homology and U-box containing protein 1), an E3 ubiquitin ligase. An increased UPR by AZM was associated with enhanced proteasome activity. AZM suppressed lung fibrosis development induced by BLM with concomitantly reduced NOX4 protein levels and enhanced proteasome activation. These results suggest that AZM suppresses NOX4 by promoting proteasomal degradation, resulting in inhibition of TGFB-induced myofibroblast differentiation and lung fibrosis development. AZM may be a candidate for the treatment of the fibrotic lung disease IPF.